Application of the Criminal Law for Distribution of Illegal Drugs by Business Actors Without a License - Husni Akhmad Husein; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Access to these drugs is an important part of a drug control system aimed at protecting people from the risks of unsafe or inferior use of drugs. Still, there are serious concerns regarding the illegal transmission of drugs or without approval in many countries. The circulation of arms and the issues associated with illegal drugs has significantly negative effects on people's health and economies. Illegal drugs are often involved in illegal trade and organized crime, which contributes to increased crime and social instability. The methods used in this study are a type of normative that focuses on laws and rules that already exist in legislation. To ensure that people can easily obtain safe, qualified and effective drugs. To achieve this, it requires cooperation and coordination between government, drug enforcement agencies, law enforcement, and other related sectors. The goal is to tackle the challenges associated with illicit drugs and provide society with optimal health protection.